2015
DOI: 10.1111/idj.12142
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and its related factors in Korean dentists

Abstract: This study suggests that burnout is a common problem in Korean dentists and that occupational calling and willing to reselect a dentistry as a job are important factors for managing burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 18 publications
6
48
1
4
Order By: Relevance
“…Considering the burnout associated with job-related characteristics, burnout varied significantly based on whether or not the respondents worked overnight, whether or not they worked monotonously, the number of years of practice and the number of hours worked per day. A similar result was observed in previous studies, 15 27 28 in which high burnout was related to heavy workload and job-related stress.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the burnout associated with job-related characteristics, burnout varied significantly based on whether or not the respondents worked overnight, whether or not they worked monotonously, the number of years of practice and the number of hours worked per day. A similar result was observed in previous studies, 15 27 28 in which high burnout was related to heavy workload and job-related stress.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, job satisfaction showed a significant positive relationship with psychosocial stress, sleep quality, depression and anxiety. Previous research revealed a negative relationship between job satisfaction and job burnout. Jager et al .…”
Section: Discussionmentioning
confidence: 96%
“…The mean scores of the three subscales (EE, DP, and PA) of MBI of studies in Korea, 8 Northern Ireland, 9 UK, 10 Dutch, 21 and Hong Kong doctors 11 are shown in Figure 3 for comparison. Generally speaking, the mean scores of EE and DP of dentists in Hong Kong were lower than those in other countries while mean PA score was in between.…”
Section: Maslach Burnout Inventory-human Services Survey and Level Ofmentioning
confidence: 99%
“…3 Maslach and her colleague 5,6 have studied the burnout syndrome for many years and devised a measurement tool-the Maslach Burnout Inventory-Human Services Survey (MBI-HSS). 4,7 Although some studies of burnout have been conducted among dentists using the MBI-HSS, 1,[8][9][10] most studies on stress and burnout in health professions have focused on physicians [11][12][13] and nurses. 14,15 In 2001, a survey was conducted to investigate the sources of occupation stress among dentists in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%